Comparative study of the effect of infrastructure development on economic growth in developing countries - SUH, Dongil (KDI School, 2017)
The purpose of this paper is to evaluate the impact of investment in various infrastructure sectors on economic growth in developing countries. Infrastructure would be interpreted in a wide sense. In this paper, infrastructure is confined to Telecommunications, Energy, Transportation and Water and Sanitation sectors. The author used a panel data set covering a panel of 113 countries from 2005 to 2015. The study found that infrastructure development generally has been effective in facilitating economic growth.
Thesis(Master) --KDI School:Master of Public Policy,2017